The energy metabolism of dyskinetoplastic Trypanosoma parasites - Ebenstreitová, Julie (Jihočeská univerzita, 2023)
Trypanosoma brucei strains that lack their mitochondrial DNA (dyskinetoplastids) are dependent on the reverse activity of the ADP/ATP carrier (AAC) to provide an electrogenic mitochondrial membrane potential (m). Since the intensity of the m and the mitochondrial ATP/ADP ratio dictate the direction of the ADP/ATP carrier, we hypothesize that mitochondrial ATP levels will be kept low in these parasites. Therefore, we analyze the m and parasite viability when we stimulate mitochondrial substrate-level phosphorylation in these dyskinetoplastids.
The energy metabolism of dyskinetoplastic Trypanosoma parasites
Keywords: Trypanosoma brucei; dyskinetoplastid; bioenergetics; substrate-level phosphorylation; ATP; Trypanosoma brucei; dyskinetoplastid; bioenergetics; substrate-level phosphorylation; AAC